The Effect of G-ORS Along With Rice Soup in the Treatment of Acute Diarrhea in Children: A Single-Blind Randomized Controlled Trial - Kianmehr; Saber; Moshari; Ahmadi; Basiri-moghadam (Kashan University of Medical Sciences, 2016)
Background The world health organization guidelines for treatment of diarrhea in children emphasize on continued feeding together with prescription of oral rehydration solution (ORS) and supplementary zinc therapy. However, conflicting viewpoints exist regarding the optimal diet and dietary ingredients for children with diarrhea. Moreover, few studies have investigated the effect of rice soup along with ORS in the treatment of this disease. Objectives This study aimed to explore effects of simultaneous taking of glucose oral rehydration solution (G-ORS) and rice soup in the treatment of acute diarrhea in 8 to 24-month-old children. Patients and Methods This single-blind controlled clinical trial was conducted in the pediatric ward of 22nd of Bahman hospital, Gonabad, Iran between June 2013 and February 2014. Forty children aged 8-24 months with acute diarrhea were randomly assigned into an intervention group (G-ORS plus rice soup group) comprising 20 babies and a control group (G-ORS) of 20 children based on balanced blocking randomization. The variables under investigation were diarrhea duration, patient hospitalization, need for intravenous (IV) fluids and stool output frequency. Data was analyzed using independent samples t and chi-square test. Results At the end of study, the time for treating acute watery diarrhea in the intervention and control groups were 21.10 ± 8.81 and 34.55 ± 5.82 hours (P < 0.001) and hospital stay were 34.05 ± 6.62 and 40.20 ± 6.32 hours (P = 0.005). Moreover, stool output frequency were 4.20 ± 0.95 and 8.00 ± 1.37 (P < 0.001) in the first 24 hours, and 2.18 ± 0.60 and 2.80 ± 0.76 (P = 0.03) in the second 24 hours of treatment in intervention and control groups, respectively. Conclusions Rice soup regimen was highly effective and inexpensive in the treatment of acute diarrhea in children. Thus, in addition to the common treatment by G-ORS, rice soup can be consumed simultaneously with G-ORS.